NON-ATHEROSCLEROTIC OBLITERATION OF BILATERAL SUPRACLINOID INTERNAL CAROTID ARTERIES; A CLASSIC CASE OF MOYAMOYA DISEASE - Ullah, Saad; Siddiqui, Anas Ahmed; Alkilani, Waseem Zaid; Khan, Noman Ahmed Jang; Siddiqui, Hafiz Umair (Journal of Ayub Medical College Abbottabad, 2017)
Moyamoya disease is an idiopathic progressive vasculopathy of distal internal carotid artery and circle of Willis which leads to the development of characteristic smoky appearance of the vascular collateral network on angiography. With the highest reported incidence among Japanese population, it has been under recognized as a cause of cerebrovascular accidents in Western countries. Here we report a case of a young 20-year-old Caucasian woman who presented to the emergency department with expressive aphasia, right arm weakness and numbness for three days. Imaging modalities confirmed Moyamoya disease. Keywords: internal carotid artery; circle of Willis; cerebral angiography